Process evaluation of a pragmatic feasibility trial on smokeless tobacco cessation intervention delivered in dental hospitals - Shaista Rasool; Fiona Dobbie; Zohaib Khan; Richard Holliday; Fatima Khalid; Tuba Khan; Linda Bauld (BMC, 2024)
Abstract Background Article 14 of the WHO 'Framework Convention on Tobacco Control' recommends, that all oral healthcare providers provide support for tobacco cessation, to all patients. Despite evidence on the effectiveness of tobacco cessation interventions in dental settings, implementation remains low in most high-burden countries like Pakistan. A pragmatic pilot trial of a dentist-delivered behavioural support intervention for smokeless tobacco (ST) cessation, was conducted in dental hospitals in Pakistan. This paper presents the findings of the process evaluation of the trial. Methods A mixed-method process evaluation of a multi-centre randomised control pilot trial of dentist-delivered behavioural support intervention ST cessation was conducted. The intervention included three sessions namely: pre-quit, quit and post-quit sessions. The process evaluation involved: semi-structured interviews with trial participants (n = 26, of which dental patients were n = 13 and participating dentists were n = 13 conducted from June-August 2022); and fidelity assessment of audio recordings of the intervention sessions (n = 29). The framework approach was used to thematically analyse the interview data. Results Overall the trial procedures were well accepted, however, young patients expressed uneasiness over revealing their ST use status. The intervention was received positively by dentists and patients. Dentists identified some challenges in delivering behavioural support to their patients. Of these, some were related to the contents of the intervention whereas, others were related to the logistics of delivering the intervention in a clinical setting (such as workload and space). Acceptability of the intervention resources was overall low amongst young patients as they did not take the intervention resources home due to fear of their family members finding out about their ST use. The intervention was successful in achieving the intended impact (in those who engaged with the intervention), i.e., change in the patients' ST use behaviour. Giving up ST with the aid of behavioural support also had an unintended negative effect i.e., the use of harmful substances (cannabis, cigarettes) to give up ST use. Patients' satisfaction with their dental treatment seemed to influence the intervention outcome. Conclusion While there are many variables to consider, but for the participants of this study, behavioural support for abstinence delivered through dentists during routine dental care, appears to be an acceptable and practical approach in helping patients give up ST use, in a country like Pakistan, where negligible support is offered to ST users.